Структурированность как свойство юридической конструкции финансово-правовых институтов (на примере налогового права Украины) - Vakaryuk, Lyudmyla; Babin, Igor (Societas et Iurisprudentia, 2017)
The main principle of structuring the legal construction of financial law as a system object are predetermination of its structure and internal arrangement by final purpose and properties of elements, provision and support of its functionality as system as a whole. The latter is just achieved due to the existence of links different in content, nature and peculiarities between individual elements of legal construction of financial law institutes, groups of elements among themselves as well as with the external environment. An important element of research in this area creates consideration of positive experience and scientific developments of scientists from foreign countries. The paper shows the development of category “legal construction of the financial and legal institute” in jurisprudence, financial and legal science and legislation. On the example of tax law – one of the key institutes for the financial law system, the essence of structural, functional and genetic links of financial law institutes is revealed while the law of optimality of the structure of legal constructions of financial law is formulated.
Structuredness as Property of Legal Construction of Financial and Legal Institutes (оn Example of Tax Law of Ukraine)
Keywords: Юридическая конструкция; финансово-правовой институт; структурированность; свойство; структурные связи; функциональные связи; генетические связи; налоговое право; Украи- на.; Legal Construction; Financial and Legal Institute; Structured- ness; Property; Structural Links; Functional Links; Genetic Links; Tax Law; Ukraine.; Юридическая конструкция; финансово-правовой институт; структурированность; свойство; структурные связи; функциональные связи; генетические связи; налоговое право; Украина; Legal Construction; Financial and Legal Institute; Structuredness; Property; Structural Links